A numerical method to investigate the temperature behavior of spiral bevel gears under mixed lubrication condition. (25th January 2019) - Gan, Lai; Xiao, Ke; Wang, Jiaxu; Pu, Wei; Cao, Wei
Highlights: Mixed EHL and FE method based on thermal analysis are integrated to predict the temperature. A calculation method of heat flux is presented in point contact region. Convective heat transfer coefficients of different surfaces are calculated in detail. The bulk and flash temperature fields in mixed lubrication are clearly studied. The major high temperature zone is closely to tooth root due to large sliding velocity and contact load. Abstract: Thermal behaviors under mixed lubrication regime are closely to the load-carrying capacity of spiral bevel gears, especially, in heavy load and high speed. In order to analyze the bulk and flash temperature behaviors, this paper proposes a numerical method which integrates the mixed elastohydrodynamic lubrication model with a finite element method based on thermal analysis. Heat generation in mixed lubrication regime is determined as functions of the applied load, sliding velocityand friction coefficient. The friction is solved by recently developed mixed elastohydrodynamic lubrication model with the consideration of surface roughness and arbitrary entrainment angle. Heat transfer analysis is conducted by application of the time- and position-varying heat flux and convection coefficient boundary condition on single tooth finite element model. The results clearly show that the major high temperature zone for bulk temperature is located nearby tooth root and the temperature in boundary lubrication is more serious compared with mixed lubrication. The edge contact at the tooth top leads to severe high temperature. The flash temperature behavior in entire rotation period indicates the influence of thermal characteristics on risk of scuffing.